Metabolic syndrome in women in the menopausal period - Stachowiak, Grzegorz; Zając, Agnieszka; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Metabolic syndrome (MetS) – whose existence is sometimes denied – is prevalent within the menopausal population, and is now a serious sociological and economic problem. The authors present the newest data on the epidemiology, diagnostics and therapy of MetS, focusing on the strain placed by menopausal hormone therapy on its individual elements.